Pemilahan Sampah: Satu Tahap Menuju Masyarakat Mandiri Dalam Pengelolaan Sampah - Paradita, Lanoke Intan (Universitas Muhammadiyah Yogyakarta, 2018)
Addressing the problem of waste management using the principle of Collect-Transport-Dump (Kumpul-Angkut-Buang) is no longer relevant since it does not solve the source of the problem that is the generated waste from household. As the highest waste generator, household waste management is crucial to reduce the waste volume dumped in the landfill. This means that active participation from the community is a must in waste management and for the community to know how to sort the waste and be able to do it is a necessity. The community service discussed in this article is one of the efforts to improve community capacity in Dusun Sruni, Cangkringan Sub-district, Sleman Regency, Yogyakarta in managing the waste generated from their household by adapting the self-managed waste management well implemented in other cities in Indonesia. The steps implemented in the com-munity service as well as the expected results are described in this article. The findings on the potential problems in educating the community-based waste management as well as futher plans activities to the sustainability of the waste management are also discussed in this article.Â Keywords: waste management, community participation, community-based waste management